Supporting children through school-based occupational therapy: A primary school teacher’s perspective - Collins, Annmarie (Marino Institute of Education, 2022)
Collaboration between education and health professionals is considered key to best practice and the application of inclusion policies. An increase in occupational therapy services within mainstream schools in recent years has led to occupational therapists working closely with teachers to integrate a shared goal of supporting the educational outcomes of children with additional needs. However, an increase in occupational therapy-teacher collaboration has also begun to highlight the complexity of a collaboration process formed by professionals with conflicting philosophies of service provision and for whom services are constructed differently. With that, it is imperative that primary teachers are professionally supported and prepared to promote inclusive educational experiences for children with additional needs through occupational therapy-teacher collaboration. Despite this, literature reveals a wide gap between current professional training and the essential knowledge that both the teacher and occupational therapist need to support inclusive education through collaborative practice. Thus, the research question that drove this study was: ‘What are primary school teachers’ perceptions of occupational therapy-teacher collaboration in facilitating inclusive education?’. Understanding primary school teachers’ views on the supports required to facilitate inclusive education through occupational therapy-teacher collaboration is crucial in improving the educational experiences and outcomes for children with additional needs. For this research project, a qualitative method was used, and data was gathered through semi-structured interviews. A total of eight primary school teachers with experience in working collaboratively with an occupational therapist were interviewed. This research identified poor access to occupational therapy services for children, a deficit of teacher training surrounding collaboration with occupational therapists and, inadequate face-to-face contact with occupational therapists, all of which impact the educational outcomes and experiences of children with additional needs. Recommendations from the study include the provision of teacher education surrounding collaborative practice with occupational therapists, better access to occupational therapy services for children and enhanced communication between teachers and occupational therapists.
Keywords: Occupational therapy for children; Occupational therapy--Practice; Children with disabilities--Education; Children with disabilities--Education--Research; Qualitative research